Hybrid Worlds of Imagination: A Comparative Analysis of Demonological Narratives among Rural Communities in Croatia and Serbia - ŠEŠO, LUKA; TRBOJEVIĆ, DANILO (Bulletin of the Institute of Ethnography SASA, 2024)
The co-authored text by Luka Šešo and Danilo Trbojević represents a unique comparative analysis of ethnographic material, relating to the form, role, and status of demonological traditions in rural communities of Croatia and Serbia. The research focuses on the relationship between folklore and the belief systems woven into the traditions of rural communities with varying demographic structures, historical experiences, cultural identities, and social realities centered around the ideas of local ontologies defined by coexistence with supernatural beings and phenomena. These communities are, in the context of this study, viewed through the lens of adaptability to coexistence with the global cultural flows of the postmodern world. Through understanding the impact of the broader social, political, and cultural context on the cultural identity of local communities, the authors aim to contribute to the understanding of the influence of changes (both local and global) in the cultural and social environment on the needs, aspirations, and logics of community members crucial for the survival, form, and status of the world of supernatural beings in rural imagination.